2020
DOI: 10.1002/emp2.12255
|View full text |Cite
|
Sign up to set email alerts
|

Validation of two pediatric resuscitation tapes

Abstract: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…One article was about injury risk factors during the 7.7 magnitude earthquake that struck Luzon in July 1990 8 . For pediatric emergency medicine, resuscitation was a common theme for 2 articles 20,22 . Other pediatric emergency medicine studies examined the effect of obesity on childhood asthma exacerbations 15 and 1 reported the rates of colonization of multidrug‐resistant gram‐negative rods in 2 neonatal ICUs 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One article was about injury risk factors during the 7.7 magnitude earthquake that struck Luzon in July 1990 8 . For pediatric emergency medicine, resuscitation was a common theme for 2 articles 20,22 . Other pediatric emergency medicine studies examined the effect of obesity on childhood asthma exacerbations 15 and 1 reported the rates of colonization of multidrug‐resistant gram‐negative rods in 2 neonatal ICUs 11 .…”
Section: Discussionmentioning
confidence: 99%
“…8 For pediatric emergency medicine, resuscitation was a common theme for 2 articles. 20 , 22 Other pediatric emergency medicine studies examined the effect of obesity on childhood asthma exacerbations 15 and 1 reported the rates of colonization of multidrug‐resistant gram‐negative rods in 2 neonatal ICUs. 11 There were 2 articles each for neurocritical care.…”
Section: Discussionmentioning
confidence: 99%